The Qur'anic phenomenon: an essay of a theory on the Qur'an by Malik Bennabi - Bennabi, Malik; El-Mesawi, Mohamed El-Tahir (Islamic Book Trust, 2004)
This book is an English translation from French and Arabic of Malik Bennabi's Book Le Phenomene Coranique/al-Zahirah al-Qur'aniyyah